Implementasi Kurikulum Merdeka dalam Membentuk Karakter Komunikatif Siswa Kelas X di MA Bahrul Ulum Tambakberas Jombang - Khodijatul Qodriyah; Didin Sirojudi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
Merdeka Curriculum is an educational initiative that gives institutions the freedom to design curricula according to the needs and characteristics of local students. This research aims to explore the implementation of this curriculum and the factors supporting the formation of students' communicative character. This research method uses descriptive with a qualitative approach used to collect in-depth data through observation, interviews and documentation. This approach is ideal for understanding the background of a problem, the social interactions of individuals, or studying groups in a holistic and natural way. The research results show that the implementation of the Merdeka Curriculum at MA Bahrul Ulum has succeeded in forming the communicative character of class Interactive and participatory learning through methods such as group discussions, presentations, and collaborative projects play a significant role in developing students' communication skills. This research provides a new contribution by examining the implementation of the Independent Curriculum in a specific context at MA Bahrul Ulum Tambakberas. Although there are similarities with previous research in focus and methodology, differences in context, challenges, and innovation in learning methods provide additional insights that are useful for the development and implementation of the Merdeka Curriculum in the future.